Satisfaction of dairy farmers towards attributes of services rendered by privately practicing para-vets at farmers’ doorstep in different states of India - KUMAR, VIKASH; MEENA, H R; SINGH, JYOTI; YADAV, RAM DEV; RAI, CHANDAN KUMAR (The Indian Journal of Animal Sciences, 2022)
A study was conducted in 2021 to measure the level of satisfaction of farmers towards para-veterinary services in four districts of India, namely Mathura, Hisar, Jaipur, and Ahmadnagar of Uttar Pradesh, Haryana, Rajasthan, and Maharashtra, respectively, using an exclusive 5-point Likert type scale. A total of 160 dairy farmers were surveyed under the random sampling method of investigation. In this study, ordered logistic regression was used to determine the predictors of satisfaction towards the delivery of animal health services to farmers. When the cause-effect relationship was analyzed, it was found that education, herd size, and annual income were negatively associated with satisfaction towards para-veterinary services. Comparative analysis of weighted mean scores for satisfaction revealed that dairy farmers were moderately satisfied with para-veterinary services in dimensions of behavioural aspects and, the cost of rendered service. When overall satisfaction of farmers towards para-veterinary services was analyzed, it was found that 44.38% of farmers were highly satisfied (having scale value of 0.42 and above on 0 to 1 point scale), followed by 32.50% respondents having a moderate level of satisfaction (value of 0.29-0.41). Para-vets need to put more effort in satisfying farmers vis-à-vis roles associated with extension and advisory services and, animal welfare aspects. Quality of service is the major factor affecting the satisfaction of the clientele. Thus, assessing the satisfaction of farmers towards para-veterinary services could be helpful in delivery of competent and efficient minor veterinary services at farmer’s door-step.